Phytochemical Composition and Pharmacological Effects of Cassia Fistula - Muhammad Saeed; Sumra Naseer; Shabbir Hussain; Muhammad Iqbal (Scientific Inquiry and Review, 2020)
Cassia fistula iswidely utilizedin conventionalmedicines against various diseases. The plantpossessesdiversepharmacological characteristicsincluding anti-tussive, hepatoprotective, anti-pyretic, anti-oxidant, anti-inflammatory, anti-cancer, anti-fungal, anti-microbial, anti-itching, anti-ulcer, anti-epileptic, anti-fertilityand wound healingcharacteristics. Its leaves and bark are used to treat skin diseases,while its roots are useful as diuretic and are used to treat tubercular glands, cardiac disorders, and ulcer. Itsfruit pulp is used as a mild laxative in numerous stomach problems. Its flowers are used to treat leprosy, abdominal problemsandfeverand its seedspossessanti-pyretic, cooling and laxativeproperties. The plant isan important source of tannins, glycosides and flavonoides, linoleic, oleic, stearic and carbohydrates. Its leaves contain glycosides, free rhein,sennosides A and B, isofavoneoxalic acidsandoxyanthraquinones derivatives,while the stem bark contains lepeol, hexacosanol, tannins and B-sitosterol. The pulp is composed of carbohydrate, arginine, protein, leucine and flavonid-3-ol-subordinates. Its pods contain astringent matter, fistulic acids, glutten matter and kaempferol,whereas its seeds are rich in malvalic acid, sterculic acid and vernolic oil. Moreover, aurantimide, ceryl alcohol, kaempferol, anthraquinonees, bianthroquonones and glycosides basic oils are present in the flower.Copyright(c) The Authors